The Relationship Between Learning Environment and Expectations and Perceptions of Graduate Students at Kerman University of Medical Sciences, Kerman, Iran - Leila Vali; Yunes Jahani; Parinaz Khalili; Morteza Sahebi (Kerman University of Medical Sciences, 2019)
Background Many factors involve in the process of education i.e., the teacher, curriculum, and learning environment. The educational climate has an exact and tangible relationship with the expectations and perceptions of students, especially students of medical sciences universities, and particularly, the graduate ones. Objectives The current study aimed at investigating the relationship between learning environment and expectations of graduate students at Kerman University of Medical Sciences, Kerman, Iran. Methods The present cross sectional study was conducted on 193 graduate students from April to July 2017. The subjects were selected by stratified random sampling and weighting methods from each faculty. Data were collected through Dundee ready education environment measure (DREEM) and SERVQUAL instruments. Data were analyzed using multiple linear regression and Pearson correlation coefficient in SPSS. P < 0.05 was considered as the level of significance. Results Among the subjects, 62.2% were male and 52.0% single; however, 76.2% were masters' students and 23.8% PhD candidates. From the students' point of view, the educational climate had a better status among the learning environment dimensions. In terms of students' expectations and perceptions of the learning environment, the tangibles and the client consideration dimensions got the highest mean scores as 42.8 and 88.8, respectively. There was a significant relationship between marital status and learning environment (P = 0.04). There was also a significant relationship between students' perception of educational services and their semester number (P = 0.04). Conclusions It is better to use student-centered viewpoints in educational planning. Students' satisfaction can be improves by providing appropriate learning spaces and optimizing the existing ones. Adjusting students' expectations by familiarizing them with the line and staff constraints in higher education can play a significant role in enhancing the quality of educational services.